Care and self-reported outcomes of care experienced by women with mental health problems in pregnancy: Findings from a national survey. (January 2018) - Henderson, Jane; Jomeen, Julie; Redshaw, Maggie
Abstract: Background: mental health problems in pregnancy and the postnatal period are relatively common and, in pregnancy, are associated with an increase in adverse outcome. It is recommended that all women are asked about their emotional and mental health and offered treatment if appropriate. Objectives: to describe the care received by women self-identifying with mental health problems in pregnancy, and to describe the effects of support, advice and treatment on outcomes in the postnatal period. Design: this study used cross-sectional survey data collected in 2014 which described women's experience of maternity care. Setting: England Participants: a random sample of women who had a live birth in January 2014. Measurements: the questionnaire asked about sociodemographic characteristics, whether women were asked about emotional and mental health in pregnancy, support and treatment offered, about postnatal wellbeing, and questions relating to attachment to their baby. Descriptive statistics and logistic regression were used to examine the associations between mental health and outcomes taking account of sociodemographic characteristics. Findings: the survey response rate was 47%. Women with antenatal mental health problems were significantly more worried at the prospect of labour and birth, had lower satisfaction with the experience of birth, worse postnatal mental health, and indications of poorer attachment to their baby. They received substantially more care than other women but they did not always view this positively. Support, advice and treatment for mental health problems had mixed effects. Conclusions: this study describes the significant additional care provided to women self-identifying with mental health problems in pregnancy, the mixed effects of support, advice and treatment, and the poor perception of staff interaction among women with mental health problems. Implications for practice: health care professionals may need additional training to effectively support women with mental health problems during the perinatal period. Highlights: Women with self-reported mental health problems during pregnancy: received a significantly greater amount of midwifery care. They had more negative perceptions of their labour care than other women. The additional support and treatment had mixed effects on mental health outcomes.